A Perspective of the Human–Grey Wolf (Canis lupus) Conflicts in Kumrat Valley, Northern Pakistan - Romaan Hayat Khattak; Liwei Teng; Tahir Mehmood; Shakeel Ahmad; Ejaz Ur Rehman; Sayantani M. Basak; Zhensheng Liu (Diversity, 2022)
In developing countries, long-term conservation goals are hindered by the high economic costs of human–wildlife conflicts. The grey wolf is one of the prominent species indulged in these incidents. We investigated human–wolf conflicts (HWCs) by interviewing 104 respondents from five villages in Kumrat Valley, northern Pakistan. The respondents declared the grey wolf a common and highly dangerous carnivore. The grey wolf was found implicated in livestock predation, inflicting a yearly economic loss of USD 9225 (USD 88.70 per household (with monthly average income of 119 USD)). Our results confirmed that livestock predation was the main reason for the community’s hostile attitude (65.38%) and perception of the grey wolf. Concerning occupation, farmers have the most significant negative attitude (p = 0.040) towards the grey wolf, yet employees (p = 0.025) and students (p = 0.030) showed a positive attitude. In addition, the other factors contributing to the negative attitude towards the grey wolf were the grey wolf sightings and livestock predation (p = 0.016 and p = 0.006), respectively. Based on the findings, we believe that predation compensation and livestock vaccination programs (as done in Gilgit-Baltistan Province of northern Pakistan as a measure of snow leopard conservation, to prevent mass mortalities of livestock due to diseases and in turn safeguarding the predator from retaliatory killing by locals in case of livestock predation) educating the populous can be very promising in minimizing the HWCs in the study area. We also recommend robust and continuous coordination between the local communities and the concerned departments.